Numerical Extraction of the True Ferroelectric Polarization Due to Switching Domains from Hysteresis Loops Measured Using A Sawyer-Tower Circuit - Bouregba, R.; Poullain, G. (Ferroelectrics, 2002)
Investigating polarization loops of ferroelectric capacitors using a Sawyer-Tower test circuit may lead to some difficulties. It is indeed well-known that the plot of D-E loops may be subject to strong deformations hindering the ferroelectric polarization due to switching domains and preventing the accurate evaluation of remanent and spontaneous polarization ( P r and P s ) and of the coercive field ( E c ). These distortions originate from the unavoidable presence of circuit elements and/or from the leaky character of the ferroelectric capacitor under test. In this paper, a suitable expression for the release of the deformations and the computation of the polarization due to switching domains is proposed including both the measurement data and the parasitic effects of all parameters of a Sawyer-Tower circuit. A numerical procedure is then presented allowing not only to restore the true shape of the ferroelectric polarization but also to determine both the resistivity and the linear dielectric constant of a ferroelectric sample. Lastly the merits of this method is demonstrated through a successful application to a ferroelectric PZT thin film.